Pengembangan Desa Wisata Menggunakan Soar Model: Studi Kasus Desa Sekaroh Lombok Timur - Kurniansah, Rizal (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Rural tourism is a priority to be developed by the government of the republic of Indonesia, thismomentum is an opportunity for villages in Indonesia to develop into tourist villages and improvethe community’s economy through tourism. Sekaroh tourism village is one of the rural tourism thathas the opportunity to become a tourist village. To make Sekaroh village a tourist village, variousstudies are needed to develop it towards a better direction. Therefore, the purpose of this researchis to formulate a strategy to develop Sekaroh village. This type of research is qualitative researchwith data collection methods used, namely observation, interviews, documentation and focus groupdiscussions. Meanwhile, the data analysis used is SOAR analysis (strength, opportunitie, aspirationand result). Based on the study that has been done, there are five recommendations in developingSekaroh village, among others, the formulation of village development planning throughcollaboration between stakeholders. Creating village branding into a marine tourism village,increasing community capacity through training in collaboration with academics and practitionersin the field of tourism, holding various tourism events regularly and scheduled into the calendar ofevents so as to attract many tourists to visit, and involving community groups in developing Sekarohvillage, with the existence of tourism activities can have a significant impact on improving theeconomy of the local community.